Fast Barrier Synchronization for InfiniBand - Hoefler, Torsten (Technische Universität Chemnitz, 2006)
Barrier Synchronization is crucial for many parallel systems. This talk introduces different synchronization mechanisms and demonstrates new approaches to leverage special hardware properties of InfiniBand to lower the Barrier latency.